KANDUNGAN BORAKS PADA PENTOL BAKSO DI KECAMATAN BALONGBENDO KABUPATEN SIDOARJO DENGAN METODE SPEKTROFOTOMETRI - Sari, Adinda Puspita; Setyawati, Herni; Zaenudin, Djelang (Jurnal Riset Kefarmasian Indonesia, 2023)
Sodium Tetraborate, also known as Borax, is a chemical compound which is a derivative of metal boron gas (B), used as an antifungal compound, wood preservative, and an antiseptic compound in cosmetics. The use of Borax as a preservative in food has been banned by the government. The purpose of this study was to help and remove the levels of borax found in meatball bulbs. Sampling was determined in Balongbendo District, Sidoarjo Regency. Analysis of the content of Borax compounds in meatball bulbs was carried out qualitatively using the flame method and the tumeric paper test. Quantitative test using the UV-Vis Spectrophotometer method. Based on the results of an analysis of 60 samples of meatball bulbs sold in Balongbendo District, Sidoarjo Regency, 1 sample was positively identified as containing a Borax compound with an average level of 0.162 ppm.